2020
DOI: 10.1088/1361-6420/abc531
|View full text |Cite
|
Sign up to set email alerts
|

Variational regularisation for inverse problems with imperfect forward operators and general noise models

Abstract: We study variational regularisation methods for inverse problems with imperfect forward operators whose errors can be modelled by order intervals in a partial order of a Banach lattice. We carry out analysis with respect to existence and convex duality for general data fidelity terms and regularisation functionals. Both for a priori and a posteriori parameter choice rules, we obtain convergence rates of the regularised solutions in terms of Bregman distances. Our r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…Remark 4.20. The same rates can be obtained for the symmetric Bregman distance (see, e.g., [47,Thm. 3.6]).…”
Section: Convergence Rates In Bregman Distancesupporting
confidence: 63%
“…Remark 4.20. The same rates can be obtained for the symmetric Bregman distance (see, e.g., [47,Thm. 3.6]).…”
Section: Convergence Rates In Bregman Distancesupporting
confidence: 63%
“…Recent studies have investigated the effect of using approximate or imperfect operators in the reconstruction [49]- [51] and the possibility to improve results with a learned correction [15], [16]. Most importantly, it is shown that under a suitable learned correction, one can accurately solve the classic variational problem.…”
Section: B a Fast Approximate Forward And Inverse Modelmentioning
confidence: 99%
“…In [23] an error bound for perturbed operators is derived under the classical source condition ∂R(u † ) ∈ range(F [u † ] * ). Under the same source condition, error bounds were also shown in [6,7,33] for more general data fidelity terms, in the first two references for perturbed operators satisfying bounds in Banach lattices. We also refer to [14] for convergence rates of wavelet thresholding methods for perturbed operators.…”
mentioning
confidence: 80%